Flux and fate of Yangtze river sediment delivered to the East China Sea - Liu, J. P.; Xu, K. H.; Li, A. C.; Milliman, J. D.; Velozzi, D. M.; Xiao, S. B.; Yang, Z. S. (Geomorphology, 2007)
Numerous cores and dating show the Yangtze River has accumulated about 1.16 x 10(12) t sediment in its delta plain and proximal subaqueous delta during Holocene. High-resolution seismic profiling and coring in the southern East China Sea during 2003 and 2004 cruises has revealed an elongated (similar to 800 km) distal subaqueous mud wedge extending from the Yangtze River mouth southward off the Zhejiang and Fujian coasts into the Taiwan Strait. Overlying what appears to be a transgressive sand layer, this distal clinoform thins offshore, from similar to 40 in thickness between the 20 and 30 m water depth to < 1-2 in between 60 and 90 m water depth, corresponding to an across shelf distance of less than 100 km. Total volume of this distal mud wedge is about 4.5 x 10(11) m(3), equivalent to similar to 5.4 x 10(11) t of sediment. Most of the sediment in this mud wedge comes from the Yangtze River, with some input presumably coming from local smaller rivers. Thus, the total Yangtze-derived sediments accumulated in its deltaic system and East China Sea inner shelf have amounted to about 1.7 x 10(12) t. Preliminary analyses suggest this longshore and across-shelf transported clinoform mainly formed in the past 7000 yrs after postglacial sea level reached its mid-Holocene highstand, and after re-intensification of the Chinese longshore current system. Sedimentation accumulation apparently increased around 2000 yrs BP, reflecting the evolution of the Yangtze estuary and increased land erosion due to human activities, such as fanning and deforestation. The southward-flowing China Coastal Current, the northward-flowing Taiwan Warm Current, and the Kuroshio Current appear to have played critical roles in transporting and trapping most of Yangtze-derived materials in the inner shelf, and hence preventing the sediment escape into the deep ocean. (c) 2006 Elsevier B.V. All rights reserved.
244vyTimes Cited:286Cited References Count:84

Sedimentary features of the Yangtze River-derived along-shelf clinoform deposit in the East China Sea - Liu, J. P.; Li, A. C.; Xu, K. H.; Veiozzi, D. M.; Yang, Z. S.; Milliman, J. D.; DeMaster, D. (Continental Shelf Research, 2006)
A predominant sigmoidal clinoform deposit extends from the Yangtze River mouth southwards 800 kin along the Chinese coast. This clinoform is thickest (similar to 40m) between the 20 and 30 m isobaths and progressively thins offshore, reaching water depths of 60 and 90 m and distances up to 100 km offshore. Clay mineral, heavy metal, geochemical and grain-size analyses indicate that the Yangtze River is the primary source for this longshore-transported clinoform deposit. (210)Pb chronologies show the highest accumulation rates (> 3 cm/yr) occur immediately adjacent to the Yangtze subaqueous delta (north of 30 degrees N), decreasing southward alongshore and eastward offshore. The interaction of strong tides, waves, the China Coastal Current, winter storms, and offshore upwelling appear to have played important roles in trapping most Yangtze-derived sediment on the inner shelf and transporting it to the south. (c) 2006 Elsevier Ltd. All rights reserved.
109ueTimes Cited:158Cited References Count:62